Bi0.5Na0.5TiO3-BiOCl composite photocatalyst for efficient visible light degradation of dissolved organic impurities. Issue 1 (February 2019) - Chauhan, Aditya; Singh Kushwaha, Himmat; Kumar, Ramachandran Vasant; Vaish, Rahul
Highlights: Composite BNT-BiOCl photocatalyst is obtained at room temperature using dilute HCl. The catalyst is free of noble-metals or unstable sensitizers. The catalyst displays high visible light activity despite having a large band-gap. The high catalytic activity is attributed to the evolution of type-B heterojunction. Surface proximity and ferroelectric parent phase also impart higher catalytic activity. Abstract: A visible light active photocatalyst is prepared by combining a non-photocatalytic ferroelectric Bi0.5 Na0.5 TiO3 (BNT) with a UV-active photocatalytic BiOCl. Photoactive BiOCl phase can be formed on the surface of parent BNT particles by a facile treatment with dilute HCl at room temperature. Phase purity, physical and chemical characterization of the as-synthesized composite catalyst was confirmed with X-ray diffraction (XRD), X-ray photoemission (XPS), fourier transform infrared and Raman spectroscopies. Scanning electron microscopy (SEM) was used to identify the particle size and morphology. The composite material displayed an effective band-gap of 3.44 eV, as confirmed through diffuse reflectance spectroscopy (DRS), with improved absorption in visible region. Photocatalytic activity of the catalyst was evaluated by monitoring degradation of Rhodamine B (Rh B) in visible light. The Rh B aqueous solution (5 mg/L) could be completely degraded in 15 min with BNT-BiOCl (15%) catalyst (1 g/L). The composite catalyst is twenty-times more active compared to phase-pure BNT. This enhancement in visible light response was attributed to the formation of a type-B heterojunction between the parent BNT and the surface formed BiOCl phases. The hypothesis was supported by direct evidence of an enhanced transient photocurrent and scavenging agent tests. This improved visible light activity of the composite catalyst is acquired by combining a non-visible light photocatalyst with a non-catalyst ferroelectric phase. This is an important observation and can be potentially extended to sensitize a host of other high band-gap materials to visible irradiation with a simple chemical step and without the use of noble metals.